Política e controle do crime: a Indústria da Tolerância em Manaus - Mota, Guilherme Gustavo Vasques (2012)
Viewing the role of media in disseminating the crime in Manaus, will be analyzed the role played by newspapers "Ten minutes" and "Manaus today" which sell their copies a day for those who live in areas of the city's outskirts, publishing news punishable acts that occurred in these areas. In the pages of newspapers, every day, there is the exposure of people involved in these events as "pests" and the proposed treatment of these, by establishing a system of "zero tolerance". This thesis attempts to prove that the performance of newspapers is driven by neoliberal rationality, power diagrams of the control society and the criminal policies "Law and Order" and "Zero Tolerance", which proposes a scheme covering the whole society in that punishes any deviation, which is in full operation in the main neoliberal democracies today. In peripheral areas, where crime is related to socio-economic, the effects of "zero tolerance" are more improved in way that produces a fracture in the current "tolerant society" rooted in international universalism, producing a new figuration of the crime pests in neoliberalism. The papers thus act as agents of the subjective processes of readers and bring different tactics to determine the behavior of those who inhabit the suburbs, by the spread of "zero tolerance" as the ideal way to fight crime in these areas, allowing the expansion of an "Tolerance Industry" in Manaus that enriches with the report of the punishment